ORGANIZATIONAL JUSTICE AND INTERNAL COMMUNICATION IN FOSTERING READINESS FOR CHANGE: A SEQUENTIAL MEDIATION MODEL - Ni Komang Suryani Wulandari; Aryana Satrya (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: This study examined how organizational justice and symmetrical internal communication were associated with readiness for change through perceived organizational support and employee engagement. Research Methodology: A quantitative cross-sectional survey was conducted among 389 civil servants at the Ministry of Primary and Secondary Education of Indonesia using purposive sampling. Data were analyzed using Covariance-Based Structural Equation Modeling (CB-SEM) with IBM SPSS AMOS. Results: Organizational justice did not have a significant direct effect on readiness for change (β = −.024, p = .753), but its effect was sequentially mediated through perceived organizational support and employee engagement (indirect effect = .211). Symmetrical internal communication had both direct and sequential indirect effects on readiness for change (indirect effect = .155). Employee engagement emerged as the strongest direct predictor of readiness for change (β = .637, p < .001). Conclusions: The findings indicate that readiness for change develops primarily through sequential psychological mechanisms, consistent with the complementary perspectives of Social Exchange Theory and Job Demands–Resources Theory. Limitations: The cross-sectional design, purposive sampling, single-institution setting, and self-reported measures limit causal inference and generalizability. Future research should employ longitudinal and mixed-method designs across multiple organizational contexts to examine how these mechanisms evolve during organizational change. Contributions: This study extends public-sector change management literature by demonstrating how organizational conditions foster readiness through sequential roles of perceived organizational support and employee engagement